The Basic Concept and Classification of Knowledge According to Malay Manuscript: A Study on Mss 2906 (B) Tibyan Al-Maram - Mamat, Mohd Anuar; Jusoh, Che Razi (Univ Malaya, Acad Islamic Studies, 2024)
Indexed by WOS